CLINICAL OUTCOME OF CHEWING GUM ON BOWEL MOTILITY AMONG PATIENTS UNDERGOING ABDOMINAL SURGERY - Karad, Amit; PK, Baviskar; Bhangale, Khilchand; Chaudhary, Amol (International Journal of Clinical and Biomedical Research, 2017)
Introduction: Postoperative paralytic ileus is one of the commonest causes of morbidity in abdominal surgeries. The aim of the present study was to evaluate efficacy of chewing gum in on bowel motility among patients who have undergone abdominal surgery. Methods: The details of patients along with diagnosis, co-morbidities, duration of anesthesia & surgery and post-operative stay were recorded. Patients that received chewing gum in addition to standard postoperative care were grouped as cases while those that received standard postoperative care were grouped as controls. The patients were observed for Peristaltic Sounds, Flatus passed, Stool Passed, return of appetite and time was recorded. Results: The study was conducted with 200 patients of which 100 each were grouped as cases and controls. Majority of the patients in Cases Group were in the age group of 40-50 years (42%). The mean age of the patients was 47.3 ±12.97 years. 7 (23.3%) patients in Cases Group had hypertension while 5 (16.7%) patients had diabetes mellitus. 8 (26.8%) patients in Control Group had hypertension while 4 (13.4%) patients had diabetes mellitus. 47 (47%) patients in Cases Group had enterocolon diseases while 43 (43%) and 10 (10%) patients had hepatobiliary and pancreatic diseases respectively. 46 (46%) patients in Control Group had enterocolon diseases while 45 (45%) and 9 (9%) patients had hepatobiliary and pancreatic diseases respectively. There was no statistical significance on comparison between the groups with respect to age, sex, co-morbidities and diagnosis. The mean duration of induction of anesthesia was 27.08±0.89 minutes and 28.16±1.14 minutes in Cases and Control Group respectively. The mean duration of surgery was 2.67±0.21 hours and 2.44±0.19 hours in Cases and Control Group respectively. The mean duration of return of Bowel Sound was significantly lesser in Cases Group as compared to Control Group (9.9±1.37 vs. 36.1±6.72 hours). The mean duration of first passage of flatus was significantly lesser in Cases Group as compared to Control Group (14.8±2.13 vs. 81.1±5.47 hours). The mean duration of time to first faeces was significantly lesser in Cases Group as compared to Control Group (36.1±7.28 vs. 107.6±6.87 hours). The mean duration of return of appetite was significantly lesser in Cases Group as compared to Control Group (19.3±2.13 vs. 87.6±5.47 hours). The duration of post-operative hospital stay was significantly lesser in Cases Group as compared to Control Group (72.1±7.28 vs. 155.6±6.87 hours). Conclusion: Gum chewing in patients undergoing abdominal surgery can be an effective intervention to facilitate the passage of flatus and feces, shorten the time to dietary intake, and shorten the length of hospital stay by promoting bowel motility. Key words: Abdominal surgery, Bowel motility, Chewing gum.